INCREASING SMEs BUSINESS VALUE THROUGH SHARIA PEER TO PEER LENDING ACCESSIBILITY EDUCATION - Hanifiyah Yuliatul Hijriah; Prinintha Nanda Soemarsono; Himmatul Kholidah; Bani Alkausar (Jurnal Layanan Masyarakat, 2023)
Efforts to increase financial inclusion and business development in the community are a synergy effort in strengthening SMEs business actors in Sidoarjo City. The active form of strengthening economic values ​​in the community also takes place in the middle of community organizations, such as the Regional Leader of Aisyiyah Sidoarjo which has the SMEs community under its guidance. These two aspects can provide mutual benefits, where the assisted SMEs in Sidoarjo have problems with financial inclusion and the accessibility of financial technology in developing businesses due to the lack of knowledge of SMEs business actors in terms of using technology because based on the survey results there are still many SMEs who do not know about access to capital through sharia peer to peer lending schemes. This condition of inadequate understanding and ability is the background of the urgency of this program to be implemented. The purpose of this community service program is to increase the capacity of SME entrepreneurs through training in the field of financial inclusion which includes financial technology, especially peer to peer lending sharia. The method chosen in this community service activity will involve training participants to actively think, discuss, and directly practice, by: 1) organizing financial inclusion education, 2) training in financial technology accessibility practices, especially peer to peer lending sharia both from the marketing aspect. and community business financing. The results that can be achieved from this activity are that SMEs business gain more insight regarding financial inclusion and increase their ability to develop businesses through the sharia peer to peer lending platform.